DIGITAL TECHNOLOGIES FOR IMPROVING THE CONTINUITY OF FOREIGN LANGUAGE TEACHING (Web of Technology: Multidimensional Research Journal, 2024)
The advent of digital technologies has brought considerable changes to education, especially the teaching of foreign languages. Language acquisition relies heavily on ongoing, flexible, and immersive learning settings. This study investigates the impact of digital technologies in improving the continuity of foreign language instruction, focussing on how these tools enable personalized learning experiences, boost collaboration, provide quick feedback, and promote constant language practice. With innovations such as online platforms, smartphone applications, and artificial intelligence-driven solutions, digital technologies provide novel ways to maintain engagement and success in language acquisition.